Effect of Prenatal Massage on Confidence Level and Stress Reduction of Pregnant Women in Preparation for Childbirth - Eka Mardiana Afrilia; Hikmah; Astrisa Faadhilah; Titin Martini (PT. Anagata Sembagi Education, 2025)
Pregnancy presents both physical and psychological challenges for women. High stress levels and lack of confidence in facing labor can negatively impact maternal and fetal well-being. Prenatal massage is recognized as a non-pharmacological intervention that helps reduce stress, improve emotional well-being, and enhance maternal confidence. This study analyzes the effect of prenatal massage on stress reduction and confidence levels in pregnant women using the Systematic Literature Review (SLR) method. Scientific articles from PubMed, ScienceDirect, and Google Scholar were reviewed, with inclusion criteria focusing on studies published in the last five years. The analysis revealed that prenatal massage significantly reduces stress by lowering cortisol levels and increasing endorphins, promoting relaxation. Additionally, it enhances psychological well-being and provides emotional support, contributing to greater confidence in facing labor. The findings suggest that prenatal massage offers substantial benefits in reducing stress and increasing maternal confidence before childbirth. Therefore, it can be recommended as part of prenatal care to support the mental and emotional health of pregnant women.